2014
DOI: 10.1902/jop.2013.130006
|View full text |Cite
|
Sign up to set email alerts
|

Association of a Common Genetic Factor, PTGER3, With Outcome of Periodontal Therapy and Preterm Birth

Abstract: These results demonstrate that the risk of unsuccessful periodontal treatment is associated with tag SNPs in specific genes that regulate the inflammatory response, one of which is also associated with sPTB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…PTGER3 is a gene associated with inflammatory response and plays a role in initiation of labor. However, another study found an increased risk of PTB in women with SNP in PTGER3 [ 44 ]. Polymorphisms in prostaglandin D receptor ( PTGDR ) also increased the risk of post-coital preterm birth in women [ 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…PTGER3 is a gene associated with inflammatory response and plays a role in initiation of labor. However, another study found an increased risk of PTB in women with SNP in PTGER3 [ 44 ]. Polymorphisms in prostaglandin D receptor ( PTGDR ) also increased the risk of post-coital preterm birth in women [ 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 ). The 13 studies were excluded for the following reasons: Surgical treatment in some cases and maintenance ( 28 - 35 ); surgical treatment in some cases and patients accepted to be <18 years old ( 36 , 37 ); anti microbial therapy with antibiotics ( 38 ); periodontal therapy performed by hygienist ( 39 ); not systematically healthy patients ( 39 ); sample consisted of patients with aggressive periodontitis ( 40 ). Hand searching of the selected journals did not reveal any additional publication.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that patients with diabetes have increased prevalence, severity and accelerated progression of periodontitis compared to those without diabetes [ 25 , 27 , 28 ]. Also, uncontrolled periodontitis negatively affects glycemic control in patients with diabetes [ 26 , 29 ], and periodontal intervention may reduce medical costs and improve health outcomes among individuals diagnosed with type 2 diabetes [ 30 , 31 ]. Designing and implementing a person-centered care model in dentistry, dental professionals are supported by a system of care that reinforces collaboration with other health care professionals in improving the overall health and well-being of person with diabetes.…”
Section: Main Textmentioning
confidence: 99%